2019
DOI: 10.3847/1538-4357/ab10db
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Star Mergers Might Not Be the Only Source of r-process Elements in the Milky Way

Abstract: Probing the origin of r-process elements in the universe represents a multi-disciplinary challenge. We review the observational evidence that probe the properties of r-process sites, and address them using galactic chemical evolution simulations, binary population synthesis models, and nucleosynthesis calculations. Our motivation is to define which astrophysical sites have significantly contributed to the total mass of r-process elements present in our Galaxy. We found discrepancies with the neutron star (NS-N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
199
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(211 citation statements)
references
References 279 publications
(433 reference statements)
10
199
1
1
Order By: Relevance
“…However, it has been reported that the evolutionary path of [Eu/Fe] predicted by NSMs is incompatible with the observed trend of disk stars due to a delayed r-process enrichment (Hotokezaka et al 2018). Thus, some authors claim the necessity of r-process-element contributions from some specific and rare core-collapse supernovae (CCSNe) that are capable of enriching gas much faster than NSMs, such as magneto-rotational SNe (Côté et al 2019) or collapsars (Siegel et al 2019). Similarly, stellar abundances of halo stars demand a fast enrichment of r-process (e.g., Mathews & Cowan 1990;Argast et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been reported that the evolutionary path of [Eu/Fe] predicted by NSMs is incompatible with the observed trend of disk stars due to a delayed r-process enrichment (Hotokezaka et al 2018). Thus, some authors claim the necessity of r-process-element contributions from some specific and rare core-collapse supernovae (CCSNe) that are capable of enriching gas much faster than NSMs, such as magneto-rotational SNe (Côté et al 2019) or collapsars (Siegel et al 2019). Similarly, stellar abundances of halo stars demand a fast enrichment of r-process (e.g., Mathews & Cowan 1990;Argast et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the end, the revealed feature suggest a large difference in [r-process/Fe] between metal-poor and metal-rich disk stars, which challenges the enrichment of Eu by NSMs. That's because r-process enrichment with the plausible DTD spanning over Gyrs for NSMs predicts only a small gradient in [Eu/Fe] with respect to [Fe/H] between the two endpoints of chemical evolution, compared to the case with fast r-process enrichment by CCSNe (Hotokezaka et al 2018;Côté et al 2019;Siegel et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…An additional important source of uncertainty comes from the nuclear inputs adopted to calculate the r-process nucleosynthesis, the most important ones being nuclear masses, β-decay rates and nuclear fission models (Eichler et al 2015;Thielemann et al 2017). Finally, the observed evolution of the r-elements in the Galaxy is hard (albeit not impossible) to conciliate with our current understanding of the occurrence rate of NSMs, regarding both the early (halo) and the late (disk) phases of the Milky Way (Tsujimoto & Shigeyama 2014;Ishimaru et al 2015;Ojima et al 2018;Côté et al 2018;Hotokezaka et al 2018;Côté et al 2018;Guiglion et al 2018;Wehmeyer et al 2019;Siegel et al 2019;Haynes & Kobayashi 2019;Côté et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…At higher metallicity, [Fe/H] > −1, the abundances of the r-process element 1 Eu have been proven impossible to reproduce with NSMs as the only r-process source when physically motivated time delay distributions are adopted (e.g. Shen et al 2015;van de Voort et al 2015;Komiya & Shigeyama 2016;Côté et al 2019;Hotokezaka et al 2018;Simonetti et al 2019). On the other hand, if short timescales of NSMs are assumed ( 10 8 yr), the abundance trend of the Milky Way disks can be readily explained (e.g.…”
Section: Introductionmentioning
confidence: 99%